Analgesic and Anti-Inflammatory Effects of 80% Methanol Extract and Solvent Fractions of the Leaves of Vernonia auriculifera Hiern. (Asteraceae) - Ashenafi E; Abula T; Abay SM; Arayaselassie M; Taye S; Muluye RA (Dove Medical Press, 2023)
Ephrem Ashenafi,1 Teferra Abula,1 Solomon Mequanente Abay,1 Mahlet Arayaselassie,2 Samson Taye,3 Rekik Ashebir Muluye3 1Department of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 2Department of Pathology, School of Medicine, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 3Department of Biomedical Research Team, Traditional and Modern Medicine Research Directorate, Ethiopian Public Health Institute, Addis Ababa, EthiopiaCorrespondence: Ephrem Ashenafi, Department of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia, Email ephremashenafiz@gmail.comBackground: The leaves of V. auriculifera has been used traditionally for the treatment of inflammatory disorders, and pain in various parts of Ethiopia. However, to our knowledge, the analgesic and anti-inflammatory activity of the crude extract and solvent fractions has never been experimentally studied.Objective: To assess the analgesic and anti-inflammatory activities of V. auriculifera leaf extract and solvent fractions in rodent models.Material and methods: Air-dried leaves of V. auriculifera were grounded and macerated using 80% methanol. The air-dried, grounded leaves were also successively extracted with ethyl acetate, and methanol. The residue was then macerated in water for 72 hr. The extract's peripheral analgesic activity, as well as the solvent fractions, were determined using an acetic acid-induced writhing test. The hot plate model was used to assess the central analgesic effect. Carrageenan-induced hind paw edema and cotton pellet-induced granuloma models were used to assess the anti-inflammatory effect in rats.Results: The 80% methanol leaf extract and solvent fractions have demonstrated significant (p < 0.05) peripheral and central analgesic activity. Both 80% methanol leaf extract and solvent fractions of V. auriculifera were found to have anti-inflammatory activity in a carrageenan-induced rat paw edema model. In the cotton pellet-induced granuloma model, all concentrations of 80% methanol leaf extract (ME), methanol fraction (MEF), and aqueous fractions (AQF) of V. auriculifera inhibited exudate and granuloma formation. Although all tested doses significantly inhibited granuloma mass formation, only the medium and highest ethyl acetate fraction (EAF) doses significantly inhibited the generation of inflammatory exudate.Conclusion: This study's findings indicate that the solvent fractions and 80% methanol extract of V. auriculifera have analgesic and anti-inflammatory properties. This study's findings not only confirm the plants' traditional claim but also provide clues for further investigation of the active principles of this plant for the development of effective and safe analgesic and anti-inflammatory drugs.Keywords: Vernonia auriculifera, analgesic, anti-inflammatory, carrageenan-induced paw edema, cotton pellet granuloma, rats